Continuous Seismic Threshold Monitoring - Ringdal, Frode; Kvaerna, Tormod (1992)
Continuous threshold monitoring is a technique for using a seismic network to monitor a geographical area continuously in time. The method provides, at a given confidence level, a continuous assessment of the upper magnitude limit of possible seismic events that might have occurred in the target area. Two approaches are presented. Site-specific monitoring: By focusing a seismic network on a specific target site, continuous threshold monitoring of that site is achieved. We optimize the monitoring capability by tuning the frequency filters and array beams to known characteristics from previous recorded events at the site. We define the threshold trace for the network as the continuous time trace of computed upper magnitude limits of seismic events in the target area at a 90% confidence level. Regional threshold monitoring: This involves conducting site-specific monitoring of a dense grid of geographical aiming points and requires the development of generic phase attenuation relationships for covering an extended geographical region. The study concludes that continuous threshold monitoring offers a valuable supplement to traditional seismic techniques used in nuclear test ban monitoring. The method may also be useful for monitoring earthquake activity at low magnitudes for sites of special interest, as well as for monitoring earthquake aftershock sequences.